2020
DOI: 10.3389/fpls.2019.01697
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Active Rhizobiome Paralleling Low Meloidogyne chitwoodi Densities in Fields Under Prolonged Organic Soil Management

Abstract: Orbiliaceae, a family harboring numerous nematophagous fungi, was not associated with the M. chitwoodi decline. A closer look revealed that a local accumulation and activation of Pseudomonas, a genus that includes a number of nematode-suppressive species, paralleled the lower M. chitwoodi densities. This study underlines the relevance of taking along both resident and active fractions of multiple organismal groups while mapping the impact of e.g. crops and soil management regimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 61 publications
2
17
0
Order By: Relevance
“…Biplot results revealed an increase in the relative abundance of ASVs assigned to Pseudomonas in J2s from all time points, and early season roots, compared to other sample classes (Fig. 3B), in line with the results of Harkes et al (48), as well as the increase in ASVs assigned to Azospirillum and Reinheimera.…”
Section: Resultssupporting
confidence: 89%
“…Biplot results revealed an increase in the relative abundance of ASVs assigned to Pseudomonas in J2s from all time points, and early season roots, compared to other sample classes (Fig. 3B), in line with the results of Harkes et al (48), as well as the increase in ASVs assigned to Azospirillum and Reinheimera.…”
Section: Resultssupporting
confidence: 89%
“…The observed taxonomic structures have common traits with the earlier described wheat and pea rhizospheric microbiomes but differ from those by shifts in abundance of few taxonomic groups only [73][74][75][76], e.g., representatives of Proteobacteria, Firmicutes and Thaumarchaeota. Analysis of the alpha-diversity showed no significant differences in diversity indices between treatments with different soil conditions, plant genotype and microbial inoculation.…”
Section: Rhizosphere Bacterial Communitiessupporting
confidence: 64%
“…During this process of increased microbial activity in plant rhizosphere, the selection of some specific microorganisms has been observed, leading to the buildup of plant-specific community in the rhizosphere (Hu et al, 2018). A recent study suggested that enrichment of members of bacterial families known for P-solubilizing, such as Rhizobiacea, Enterobacteriaceae, Pseudomonadaceae, and Burkholderiaceae, has been observed in the pea rhizosphere (Harkes et al, 2020). In comparison to cereals, legumes pose a much stronger influence on the selection of rhizosphere microbiome (Hamel et al, 2018;Harkes et al, 2019Harkes et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%